2000
DOI: 10.1034/j.1600-0536.2000.043006327.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand eczema in metalworker trainees – an analysis of risk factors

Abstract: The present study, as part of PROMETES (Swiss Prospective Metal Worker Eczema Study), was performed to examine risk factors for the development of occupational hand dermatitis in metal-worker trainees. Since this disease is very common, a high standard of preventive measures is necessary, especially for persons with an endogenous disposition for the development of eczema, e.g., atopics. Within the cohort of 201 healthy young men, 47 (23%) showed at least mild signs of hand eczema at 1 point of the 2.5 year obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
4
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 8 publications
5
100
4
6
Order By: Relevance
“…Three studies found a statistically significant positive association between tobacco smoking and HE with respect to prevalence (27)(28)(29), and one found no clear association, but a slightly increased risk of HE in heavy smokers in one subgroup, along with a potential protective association in another subgroup (30). Three studies found no association between tobacco smoking and HE prevalence (31)(32)(33), but, in one of these, smoking was linked to severe eczema (32), and in another non-smoking was linked to more severe eczema (33). For information regarding adjustment for risk factors in each of the articles, see Table 1.…”
Section: Results Of Studies On He and Tobacco Smoking In Occupationalmentioning
confidence: 95%
See 2 more Smart Citations
“…Three studies found a statistically significant positive association between tobacco smoking and HE with respect to prevalence (27)(28)(29), and one found no clear association, but a slightly increased risk of HE in heavy smokers in one subgroup, along with a potential protective association in another subgroup (30). Three studies found no association between tobacco smoking and HE prevalence (31)(32)(33), but, in one of these, smoking was linked to severe eczema (32), and in another non-smoking was linked to more severe eczema (33). For information regarding adjustment for risk factors in each of the articles, see Table 1.…”
Section: Results Of Studies On He and Tobacco Smoking In Occupationalmentioning
confidence: 95%
“…Berndt et al (31) performed a prospective cohort study including 201 male metalworking trainees, followed for 2.5 years from the beginning of their apprenticeship. During the observation period, 47 (23%) of the young men developed at least an early stage of HE.…”
Section: Results Of Studies On He and Tobacco Smoking In Occupationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher risk (1.5-fold) for OCD associated with respiratory atopy was also found in nurses 85) . However, the majority of studies have failed to find such associations 55,57,68,86,87) . Patients with respiratory atopy were found to have a similar barrier function and response to SLS induced irritation compared to healthy control subjects 88) .…”
Section: Atopic Diathesis and Acdmentioning
confidence: 99%
“…However, in practice several differing, more or less circumscribed definitions are used, which seriously hamper the comparison of the many studies in this field. For the development of OCD, atopic skin diathesis indicated by previous or present AD is considered as an important predisposing factor [56][57][58][59][60][61][62][63] . To assess atopic skin diathesis (ASD), a prognostically useful diagnostic score based on the accompanied signs and symptoms of AD has been proposed by Diepgen 64,65) .…”
Section: Atopic Diathesis and Icdmentioning
confidence: 99%